Development of QR Code-Based Digital Learning Media to Improve Students’ English Speaking Skill - Kasmaini, Kasmaini; Zahrida, Zahrida; Kristiawan, Muhammad; Danim, Sudarwan (Journal of English Education and Teaching, 2024)
This research is entitled Development of Digital Learning Media Based qr code (quick response) to improve the English Speaking Skills of English Language Education Study Program students FKIP Universitas Bengkulu. The population of this study is students in semester III (grades A and C) of the English language education study program FKIP UNIB. This is development research that produces digital learning media in academic speaking courses that use QR Code. There are a wide variety of QR shapes and colors used. The files included are videos, pdfs, and ms words.   The development of this teaching material uses a model ADDIE (Analysis, Design, Development, Implementation and Evaluation) developed by Dick and Carrey in 1996. The teaching materials developed are designed based on the syllabus used in this course. There are seven themes in this teaching material which are carried out for 14 meetings.